2006
DOI: 10.1080/09640560600849962
|View full text |Cite
|
Sign up to set email alerts
|

A watershed management framework for mountain areas: Lessons from 25 years of watershed conservationin Nepal

Abstract: A watershed management framework for mountain areas is based on lessons learned from watershed management experience, social and institutional learning, and the use of a watershed management program evaluation in Nepal. The lessons led to the adoption of a subwatershed-based ecosystem approach based on local participation at the subwatershed level. An integrated watershed management framework (IWMF) consisting of eight steps with three checklists was developed focusing on improvement-oriented adaptive manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…While there were benefits from structural activities, in economic and livelihood terms they were small, compared to those resulting from the conversion of land use from open grazing to protected pasture and from government forest to community forest. Treating eroding gullies did not result in land use changes and often failed after the first season of monsoon rains (Fleming 1983) Economic analyses of other projects in the Middle Hills of Nepal showed that the costs of building torrent control structures, treating landslides and building embankments in riparian zones far exceeded the economic benefits valued in terms of conserved agricultural land (Achet and Fleming 2006).…”
Section: Economic Analysis Of the Costs And Benefitsmentioning
confidence: 99%
“…While there were benefits from structural activities, in economic and livelihood terms they were small, compared to those resulting from the conversion of land use from open grazing to protected pasture and from government forest to community forest. Treating eroding gullies did not result in land use changes and often failed after the first season of monsoon rains (Fleming 1983) Economic analyses of other projects in the Middle Hills of Nepal showed that the costs of building torrent control structures, treating landslides and building embankments in riparian zones far exceeded the economic benefits valued in terms of conserved agricultural land (Achet and Fleming 2006).…”
Section: Economic Analysis Of the Costs And Benefitsmentioning
confidence: 99%
“…Associated with distribution of benefits to indigenous community in REDD+ program, it is necessary to introduce knowledge on forestry business to the community as promoted by Tomaselli and Hajjar (2011). Moreover, Cronkleton et al (2011) stated that their study indicate that social forestry management can be an option in the implementation of REDD+ in Mexico, Brazil, and Bolivia.…”
Section: Water Conservation Program and Reduction Of Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Finding an accurate framework to assess the sustainability level of future and the existing decisions has become an important issue. A review of literature shows that some methodologies and tools are available to assist managers in the sustainable risk management field (Turner II et al, 2003;Freedman et al, 2004;Achet and Fleming, 2006;Kang et al, 2013). However, most of these tools are either specific to a hazard (mostly flood and coastal hazards; see McGahey et al, 2009), based on a mono-criterion approach, considering only one aspect of sustainability (e.g.…”
Section: Introductionmentioning
confidence: 99%